Revision of Hoplasoma (Coleoptera: Chrysomelidae: Galerucinae) of the Philippines, with descriptions of five new species - Bezděk, Jan (Zootaxa, 2012)
The species of Hoplasoma Jacoby, 1884, of the Philippines are revised. Eight species, including five new, are treated: H.bakeri Bezděk, sp. nov. (Sibuyan), H. konstantinovi Bezděk, sp. nov. (Mindoro), H. magellani Bezděk, sp. nov. (Mind-anao, Sulu, Samar, Panaon), H. mcgregori Bezděk, sp. nov. (Negros), Hoplasoma mindanense Medvedev, 2002 (Mindan-ao), H. philippinense Jacoby, 1894 (Luzon), H. picifemora Allard, 1888 (= H. luzonica Medvedev, 2002, syn. nov.)(Luzon) and H. semperi Bezděk, sp. nov. (“Philippines”). Lectotypes are designated for H. philippinense and H.picifemora. Photographs of the type specimen, male abdomen, female last ventrite and drawings of male genitalia are presented for all the species. A key to the species of the Philippines is provided.